2012
DOI: 10.1177/1479164112454309
|View full text |Cite
|
Sign up to set email alerts
|

High-density lipoprotein impedes glycation of low-density lipoprotein

Abstract: Glycation of low-density lipoprotein (LDL) increases its atherogenicity, but whether high-density lipoprotein (HDL) can protect LDL against glycation is not known. LDL and HDL were isolated from 32 volunteers with serum HDL cholesterol concentrations ranging from 0.76 to 2.01 (mean = 1.36) mmol/L. Glycation of LDL was induced by incubation with 0-80 mmol/L glucose for 7 days at 37°C under nitrogen in the presence of and absence of human HDL. Glycation of LDL apolipoprotein B (apoB) doubled at glucose 50 and 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…We have also shown that HDL can impede the modification of LDL by glycation in vitro , and that this anti-glycative function of HDL is more marked with HDL obtained from people with higher serum PON1 activity (Younis et al, 2013 ). We noted in these experiments that LDL is relatively resistant to glycation in the absence of oxygen, such that supraphysiological glucose concentrations are required.…”
Section: Hdl Antiglycative Activitymentioning
confidence: 87%
See 1 more Smart Citation
“…We have also shown that HDL can impede the modification of LDL by glycation in vitro , and that this anti-glycative function of HDL is more marked with HDL obtained from people with higher serum PON1 activity (Younis et al, 2013 ). We noted in these experiments that LDL is relatively resistant to glycation in the absence of oxygen, such that supraphysiological glucose concentrations are required.…”
Section: Hdl Antiglycative Activitymentioning
confidence: 87%
“…We have contributed to the notion that paraoxonase 1 (PON1), an enzyme located almost exclusively on HDL, is important in impeding oxidative modification of LDL (Mackness et al, 1991 , 1993 ; Durrington et al, 2001 ). Our recent work has focused on glycation as an atherogenic modification of LDL and this too has led us back to PON1 (Younis et al, 2013 ). Other HDL components have also been conjectured to be involved in preventing atherogenic LDL modification and evidence increasingly points to a coordination of these with PON1.…”
Section: Introductionmentioning
confidence: 99%
“…HDL-PON1 was shown recently to impede LDL glycation and lipoprotein peroxidation. The enzyme protecting effect augmented with increased PON1 content [8].…”
Section: Introductionmentioning
confidence: 98%
“…These tasks include to protect lipoproteins and cells against oxidative stress and also to inhibit atherogenesis and lipoprotein peroxidation . This protective effects of PON1 are associated with the enzyme level in the serum . Recent studies found that PON1 levels have low in patients with atherosclerosis, diabetes, and hypercholesterolemia and overexpression of PON1 especially impedes the development of cardiovascular diseases.…”
Section: Resultsmentioning
confidence: 99%